Assessing business and financial risks: A case study of Sapura Energy bhd in the oil and gas industry - Amin, Ikmal Arif Mohamad; Hadi, Abdul Razak Abdul (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
The study extracts documentary evidence from financial reports and deploys descriptive statistics analysis to understand Sapura Energy’s financial profiles and competitive edges. This study also deploys descriptive statistics and trend analysis to understand Sapura Energy’s financial profiles and competitive edges. Sapura is one of the local pioneers that provides engineering services in the entire value chain for oil and gas exploration, development, and production. Sapura Energy was a national pride once as it was geared towards becoming a sustainable global energy and engineering solutions company. However, Sapura Energy’s underperformance for the past 10 years has become debatable. Sapura is experiencing a burdensome debt from large overdue payments to vendors and some operational issues exacerbated by the COVID-19 pandemic from 2020 to 2021. Sapura should consider downsizing its business operations and recalibrating its capital structure to mitigate most business and financial risks. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.